FORMATION AND FUNCTIONAL SIGNIFICANCE OF A MOLECULAR COMPLEX DERIVED FROM THE SECOND AND THE FOURTH COMPONENT OF HUMAN COMPLEMENT - Müller-Eberhard, Hans J. (The Rockefeller University Press, 1967)
A functional unit of the human complement system has been delineated. It is composed of two subunits which are derived from the second (C'2) and from the fourth (C'4) component of complement. Purified C'2 and C'4 were found to interact in free solution and to form a reversible protein-protein complex. When acted upon by C'1 esterase in the presence of Mg ions, the reversible complex acquires stability and the ability to act enzymatically on the third component of complement. The trivial name C'3 convertase has been selected to denote the enzyme. Molecular weight determinations suggest that the entire C'4 molecule, but probably only a fragment of the C'2 molecule, are incorporated into C'3 convertase. Prior treatment of C'2 with iodine led to enhanced stability and activity of the enzyme. It was shown that the cell-bound form of C'3 convertase is cytolytically active and that the free enzyme is able to induce lysis from the fluid phase of erythrocytes from patients with paroxysmal nocturnal hemoglobinuria. Evidence was presented that action of C'3 convertase on C'3 results in fragmentation of the molecule.